ULTRASOUND SONOGRAPHY OF FETAL DEVELOPMENT DURING FETOGENESIS OF EDILBAY EWES IN DIFFERENT MULTIPLICITY GESTATION - Smagulov, D. B.; Tulebayev, B.; Arystanova, A. K.; Makhimova, Zh. N. (Ғылым және білім №1, 2020)
The article deals with results of ultrasound study fetogenic growth in embryonic ontogenesis uterine young animals belonging to edilbay sheep breed, i.e. by ultrasound scanner is considered in Aimeken farm West Kazakhstan region. By recognizing the interior of living organisms at various stages ontogenesis, it is possible to study the development of organs, tissues, and morpho-physiological structures, biochemical composition and determine the factors that affect them. Currently, ultrasound sonography is a very popular and efficient method. It allows at its stage not only to identify the development of embryo, but also identify other pathological conditions offspring. Therefore, during the experiment, animal pregnancy shows positive result. According to the data obtained, their pregnancy passes normally, at each stage, obstetric parameters increased, such as diameter of fetal shell, biparietal head size and diameter transverse size fetus. As the diameter of head and body fetus increases, respectively, length coccyx also observes growth dynamics. Keywords: fetal shell diameter, labor-coccyx length, biparietal head diameter, head diameter, transverse size diameter, body diameter, growth charts, heart rate. В статье приведены данные по изучению фетогенеза эмбрионального развития курдючных ягнят методом ультразвуковой сонографии. Для проведения опытов в качестве объектов исследования отобраны грубошерстные курдючные овцы специализированного мясо-сального направления продуктивности КХ «Аймекен» Акжаикского района Западно-Казахстанской области. Согласно методике подопытные овцематки были разделены на 5 групп в зависимости от разной кратности их суягности. В результате которого были определены параметры онтогенеза ягнят плодного периода развития. В настоящее время ультразвуковая сонография является очень популярным и эффективным методом. Это позволяет не только выявить развитие эмбриона, но и выявить другие патологические состояния потомства. Согласно полученным данным, их беременность проходит нормально, на каждой стадии акушерские параметры увеличивались, такие как диаметр оболочки плода, размер бипариетальной головки и диаметр поперечного размера плода. По мере увеличения диаметра головки и тела плода соответственно увеличивается и динамика роста.
Keywords: журнал кксон; рк; научный журнал; периодическое издание; отечественное издание; овцеводство; курдючные ягнята; эмбриональное развитие ягнят; ультразвуковая сонография; fetal shell diameter; labor-coccyx length; biparietal head diameter